(untitled) (Journal of Comparative Research in Anthropology and Sociology, 2025)
The substantial and continuous influx of Romanian emigrants who have maintained ties with their homeland and/or engaged in a form of migratory commute contribute to the cultural exchanges evident in social values. The current study presents an analysis conducted as part of the research on the dynamics of social values in Romanian communities in the United States. A total of 18 semi-structured interviews were conducted online with stable members of Romanian communities in the American diaspora. The qualitative data from the interviews was processed using a coding software, which helped discover indicators of values as important topics for migrants. The analysis of the interviews revealed the existence of two categories of values with a significant impact at the community level and implications beyond the geographical, economical, and cultural boundaries. These were identified as materialist-economic and cultural-identity. The two lenses through which migrants view their country of origin afford a deeper understanding of the process of change at the level of mentality and values. Also, the data reveals the stages through which these changes occur, and the types of connections established between the Romanians who emigrated and those remaining in Romania. There are three key factors in the process of changing social values specific to Romanian immigrant communities in America: triggering (related to well-being, such as values related to basic needs), mediating (related to cultural values, valuing tradition and customs) and repurposing (an alternative interpretation of values in the context of solving the signaled problems). These factors facilitate the rapid change of values for migrants.